Mitochondrial area in the cytoplasm of mice hepatocytes on diet high with fat treated with metformin - Milošević, Sara (Medicinski podmladak, 2025)
Introduction: At the cellular level, it is well acknowledged that diabetes is escorted with mitochondrial dysfunction in hepatocytes. Decreased number of mitochondria and their respiratory activity have been noticed in type 2 diabetes patients. The primary way that metformin works is thought to be due to inhibition of complex 1 respiratory chain in the inner mitochondrial membrane, and recent research has suggested that metformin, at therapeutically relevant concentrations, increases mitochondrial membrane potential, mitochondrial respiration and ATP levels in hepatocytes. C57BL/6J mice on high-fat diet (HFD) are a commonly used model for type 2 diabetes and metabolic syndrome. The aim: Examination of the area occupied by mitochondria in HFD fed mice hepatocytes without treatment and treated with metformin.Material and methods: C57BL/6J male mice were divided into two experimental groups that received high-fat food. During the last month, once a day, one group of mice was given metformin. After 6 months, mice were sacrificed and liver samples were handled for TEM. Photomicrographs were analyzed using ImageJ software by measuring the area of all visible mitochondria. Statistical analysis was done by the SPSS program using Student's T test.Results: Analysis of the hepatocyte ultrastructure revealed that the mitochondria were mostly spherical or oval in shape and of normal morphology, with no noticeable differences among the experimental groups. The average size of mitochondria in the group of HFD mice was 4.75 ± 0.25μm, and in the group of HFD mice that received metformin 4.44 ± 0.6μm. There were no statistically significant differences in mitochondrial size across the research groups. (p> 0.05).Conclusion: In light of the findings, it may be said that in animals on a high fat diet metformin does not change the area of mitochondria.
Keywords: diabetes; hepatocytes; mitochondria; metformin; HFD